Can virtual events achieve co-benefits for climate, participation, and satisfaction? Comparative evidence from five international Agriculture, Nutrition and Health Academy Week conferences. Issue 2 (February 2022) - Yates, Joe; Kadiyala, Suneetha; Li, Yuemeng; Levy, Sylvia; Endashaw, Abel; Perlick, Hallie; Wilde, Parke
Summary: The advancement of science and evidence-based solutions for planetary health increasingly require interdisciplinary and international learning and sharing. Yet aviation travel to academic conferences is carbon-intensive and expensive, thus perpetuating planetary health and equity challenges. Using data from five annual international Agriculture, Nutrition and Health Academy Week conferences from 2016 to 2020, we explore whether moving to virtual conferencing produced co-benefits for climate, participation, attendee interaction, and satisfaction. We report on: absolute number of attendees, proportion of attendees from countries of different income levels, number of participants at social events, aviation CO2 emissions, and overall ratings of the event by participants. Transitioning online resulted in large reductions in travel-related aviation CO2 emissions, alongside increased attendance—including among attendees from low-income and middle-income countries. This was achieved without a major change in the participant rating of the event. However, the online format resulted in lower participation in conference social events. The urgency of reducing CO2 emissions in pursuit of planetary health and improving equity in scientific exchange requires new modalities of academic conferencing. This study indicates that co-benefits can be achieved when transitioning online. Challenges exist for virtual events, such as emulating the intangible facets of in-person interactions, overcoming time-zone limitations, and digital divides.